دور ممارسات السلطة في تحقيق كفاءة أداء الموارد البشرية داخل المؤسسة العمومية الصناعية - بخوش, وليد; نصيب, أسماء (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الورقة البحثية إلى الكشف عن الدور الذي تلعبه ممارسات السلطة في تحقيق كفاءة أداء الموارد البشرية داخل المؤسسة العمومية الصناعية –مصنع الإسمنت بالماء الأبيض- "ولاية تبسة" وتمت الدراسة الميدانية بطريقة المسح الشامل على "171عامل" وبعد المعالجة الإحصائية خلصت الدراسة إلى أن ممارسة السلطة بأساليب إيجابية مرنة تزيد من كفاءة أداء المورد البشري انطلاقا من أن الإشراف الموجه نحو العمال يساهم في نمو مستوى مهاراتهم الوظيفية وأن القيادة الديمقراطية تساهم في ارتفاع معدل إنجازهم إلى جانب تطبيق مبدأ اللامركزية في العمل يساهم في زيادة الفرص في تحمل مسئولية أعمالهم في حين أن الاتصال الصاعد يساهم في تحقيق الدقة على مستوى أداءهم داخل المؤسسة . Abstract: This study aims to reveal the role that power practices play in achieving human resource performance in public industrial society. The field study opted for a global survey of "171 workers" during the academic year (20-20-2019). After statistical processing. The study concluded that the exercise of power by positive and flexible methods increases the efficiency and performance of human resources, based on the fact that supervised supervision of workers contributes to the growth of their level of professional skills and that democratic leadership contributes to a high rate in their performance. Besides the application of the principle of decentralization in the work which contributes to increase the opportunities to take responsibility in their actions. As well as, bottom-up communication helps to achieve precision in the level of their performance within the organization
مقال
Keywords: ممارسة السلطة ; كفاءة أداء الموارد البشرية ; المؤسسة العمومية الصناعية; The role of exercising power; achieving human resource performance; public industrial society